PENGARUH DISIPLIN KERJA DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN BAGIAN MEDIS PUSKESMAS BAGAN PUNAK ROKAN HILIR - Ika Yuni Krisnawati; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research was conducted at the Bagan Punak Rokan Hilir Health Center, located in Bangko District, Bagan Readyiapi, Rkan Hilir, Riau. Employees are operational supporting factors that carry out all activities. An increase in the number of violations can have a negative impact, namely the occurrence of obstacles in achieving organizational goals. The high level of violations can be an indication that the lack of discipline and work experience of medical employees causes the low performance of medical employees at the Bagan Punak Health Center. In this research, the method used is descriptive quantitative method with SPSS program. Due to the number of population members below 100 people, all members of the population were used as research respondents, as many as 42 people. Hypothesis testing uses simple linear analysis and multiple linear analysis by showing the results that work discipline and work experience have a significant effect on employee performance. By calculating the coefficient of determination (R2) simple discipline on employee performance obtained R square value of 0.565 or 56.5% and work experience on employee performance obtained R square value of 0.507 or 50.7%. Calculation of the multiple determination of work discipline and work experience on employee performance obtained an R square value of 0.635 or 63.5%. This shows that the percentage contribution of work discipline and work experience variables on employee performance is 63.5% while the remaining 36.5% is influenced by other variables that the researcher did not include in this study. Keywords: Work Discipline, Work Experience and Employee Performance